Subtropical Dust Storms and Downslope Wind Events. Issue 19 (6th October 2017) - Pokharel, Ashok Kumar; Kaplan, Michael L.; Fiedler, Stephanie
Abstract: We performed detailed mesoscale observational analyses and Weather Research and Forecasting (WRF) model simulations to study the terrain‐induced downslope winds that generated dust‐emitting winds at the beginning of three strong subtropical dust storms in three distinctly different regions of North Africa and the Arabian Peninsula. We revisit the Harmattan dust storm of 2 March 2004, the Saudi dust storm of 9 March 2009, and the Bodélé Depression dust storm of 8 December 2011 and use high‐resolution WRF modeling to assess the dynamical processes during the onset of the storms in more depth. Our results highlight the generation of terrain‐induced downslope winds in response to the transition of the atmospheric flow from a subcritical to supercritical state in all three cases. These events precede the unbalanced adjustment processes in the lee of the mountain ranges that produced larger‐scale dust aerosol mobilization and transport. We see that only the higher‐resolution data sets can resolve the mesoscale processes, which are mainly responsible for creating strong low‐level terrain‐induced downslope winds leading to the initial dust storms. Key Points: Downslope winds resulted in strong low‐level vertical wind shear, which interacted with the development of near‐surface positively buoyant air during the morning and generated significant turbulence kinetic energy The strong and gusty winds caused moderate meso‐γ‐ to β‐scale dust storms as an early stage of precursor to later severe dust storms that affected large areas